Vaterite deposition on biodegradable polymer foam scaffolds for inducing bone-like hydroxycarbonate apatite coatings - Boccaccini, Aldo R.; et al. (Journal of Materials Science: Materials in Medicine, 2007)
Hydroxycarbonate apatite (HCA) coatings on the surface of bioresorbable materials for bone tissue engineering scaffolds were produced using macroporous poly(DL-lactide) (PDLLA) foams impregnated by calcium carbonate in vaterite crystalline form. Stable and homogeneous vaterite deposition on PDLLA foams was achieved using a slurry dipping technique. In vitro studies in simulated body fluid (SBF) were performed to induce formation of (HCA) on the surface of vaterite/PDLLA composite foams. HCA was detected after immersion of foams in SBF for 7 days. Hence, depositing vaterite on materials followed by immersion in SBF is confirmed to induce HCA coatings on the surface of the material. The HCA coated, bioactive and resorbable PDLLA foams are intended for use as bone tissue engineering scaffolds. © 2007 Springer Science+Business Media, LLC.
UnivIS-Import:2015-03-09:Pub.2007.tech.IW.LM.vateri